Platelet and Fibrinogen Survival with 75Se Selenomethionine in Acute Infectious Hepatitis - Musumeci, S; D’Agata, A; Panebianco, M. G; LI Volti, S (Thrombosis and Haemostasis, 1975)
Simultaneous platelet and fibrinogen survival with 75Se selenomethionine was determined in eight patients with acute infectious hepatitis of intermediate severity. Fibrinogen survival alone was estimated in another nine patients, seven of whom were receiving heparin treatment. Platelet survival was found to be normal (7–9 days) in seven of the 8 patients ; it was reduced (4.6 days) only in one patient, who was also affected by measles. Fibrinogen survival was markedly reduced (1–3.7 days) and fibrinogen turnover sharply increased (0.59–2.80 mg/ml/day) in all but one patient, who had thalassaemia major, with normal fibrinogen survival and fibrinogen turnover. Heparin treatment did not affect either platelet survival or fibrinogen turnover. In all patients the coagulation defect was mild and no sign of disseminated intravascular coagulation or of increased fibrinolytic activity could be demonstrated by routine tests. These results are consistent with the hypothesis that in acute infectious hepatitis the decreased survival and increased turnover of fibrinogen might be due to a pathological pathway of defibrination independent of thrombin or plasmin.